2007
DOI: 10.1111/j.1445-5994.2006.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E treatment on peroxisome proliferator‐activated receptor‐α expression and insulin resistance in patients with non‐alcoholic steatohepatitis: results of a pilot study

Abstract: Vitamin E treatment, in addition to its previously shown beneficial effect by suppressing oxidative stress, may also achieve improvement by reducing IR and PPAR-alpha expression in NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
1
46
0
6
Order By: Relevance
“…Note that serum ICAM-1 levels were significantly elevated in patients with NASH and patients diagnosed with NAFLD compared with healthy subjects . The importance of oxidative stress in vivo is further supported by findings in animal models and clinical studies suggesting that treatment with antioxidants, e.g., vitamin E, may alleviate steatosis and the extent of liver injury (Robertson et al, 2001;Dufour et al, 2006;Portincasa et al, 2006;Yakaryilmaz et al, 2007).…”
Section: Organelle Toxicity In Nonalcoholic Hepaticmentioning
confidence: 71%
See 1 more Smart Citation
“…Note that serum ICAM-1 levels were significantly elevated in patients with NASH and patients diagnosed with NAFLD compared with healthy subjects . The importance of oxidative stress in vivo is further supported by findings in animal models and clinical studies suggesting that treatment with antioxidants, e.g., vitamin E, may alleviate steatosis and the extent of liver injury (Robertson et al, 2001;Dufour et al, 2006;Portincasa et al, 2006;Yakaryilmaz et al, 2007).…”
Section: Organelle Toxicity In Nonalcoholic Hepaticmentioning
confidence: 71%
“…The value for the dietary supplementation of PUFAs in NAFLD has been questioned by findings in a murine model of steatohepatitis, in which n-3 PUFAs failed to prevent the development of steatohepatitis because of accumulation of hepatic lipoperoxides (Larter et al, 2008a). Such effect, however, may be encountered by Sekiya et al, 2003;Capanni et al, 2006;Le Foll et al, 2007;Allard et al, 2008;Machado et al, 2008 340 ANDERSON AND BORLAK combination with other antioxidative strategies, such as treatment with vitamin E. Data from clinical studies had indicated that dietary supplementation with vitamin E in patients with NASH is associated with significant effects on liver transaminase levels and histopathology of NASH, and it may improve serum TNF-␣ levels (Lavine, 2000;Hasegawa et al, 2001;Harrison et al, 2003a;Kugelmas et al, 2003;Sanyal et al, 2004;Dufour et al, 2006;Yakaryilmaz et al, 2007). A combination of vitamin E with phospholipids and silymarin, an extract of milk thistle seed (silybum marianum), resulted in an improvement of hepatic steatosis (as assessed by ultrasonographic scores) and hyperinsulinemia, lowered liver transaminase levels and other indices of liver fibrosis as well as plasma levels of TGF-␤ and TNF-␣ in patients with NAFLD (Loguercio et al, 2007).…”
Section: Other Approachesmentioning
confidence: 99%
“…Vitamin E is an anti-oxidant and has been investigated to treat NASH. [124][125][126][127][128] Comparison between these trials is difficult due to varying criteria for entry into the study, different doses of vitamin E and unclear formulations of vitamin E used which could affect its bioavailability, the additional use of other anti-oxidants or other drugs and limited histologic data to assess outcomes. Also, most studies were relatively under-powered and did not meet or publish CONSORT criteria for clinical trials.…”
Section: Vitamin Ementioning
confidence: 99%
“…Yakaryilmaz gave VE (800 mg daily) on 9 patients with biopsy-proven NASH for 24 weeks, both the ALT levels and fatty degeneration were significantly improved [14]. The above studies show that VE treatment for NAFLD is beneficial, but for the reasons of small sample size, single-center and different endpoints, they are not able to provide enough evidence to assess the effectiveness of VE.…”
Section: Therapeutic Effect Of Ve Alonementioning
confidence: 87%